PENERAPAN METODE YANBU’A DALAM PEMBELAJARAN BACA TULIS AL-QUR’AN (BTQ) DI TAMAN PENDIDIKAN AL-QUR’AN (TPQ) BANI MUSLICH KADUGAJAH PANDEGLANG - Hujaemah, Neneng Siti; Budiana; Euis Ernawati (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to describe the application of the Yanbu'a method in teaching reading and writing the Qur'an at the Bani Muslich Kadugajah Pandeglang TPQ, as well as to identify the obstacles encountered and assess the effectiveness of this method in improving students' abilities. This study uses a qualitative approach with a descriptive research type. The research subjects included teachers, administrators, and students directly involved in the learning process. Data collection techniques were carried out through observation, interviews, and documentation, so that the researchers obtained a comprehensive picture of the implementation of the Yanbu'a method. Data analysis was carried out qualitatively through the process of data reduction, data presentation, and conclusion drawing. The results showed that the Yanbu'a method was implemented systematically and in accordance with the method guidelines, starting from learning the Hijaiyah letters to correct pronunciation through an individual approach. The obstacles encountered included differences in students' levels of understanding, limited learning time, and minimal guidance from parents. Nevertheless, the Yanbu'a method proved to be effective in significantly improving students' ability to read and write the Qur'an. Students became more enthusiastic, confident, and showed good progress, including students with slow comprehension. The application of the Yanbu'a method at TPQ Bani Muslich Kadugajah Pandeglang has made a positive contribution to improving the quality of Al-Qur'an learning. With a fun and systematic approach, this method can be a strategic choice in religious education at the elementary level.